Evaluation of laryngeal mask as an alternative to endotracheal intubation in cats anesthetized under spontaneous or controlled ventilation - Cassu, R. N.; Luna, SPL; Teixeira Neto, Francisco José [UNESP]; Braz, JRC; Gasparini, S. S.; Crocci, A. J. (Blackwell Publishing, 2004)
Objective To compare the cardiorespiratory effects and incidence of gastroesophageal reflux with the use of a laryngeal mask airway (LMA) or endotracheal tube (ET) in anesthetized cats during spontaneous (SV) or controlled ventilation (CV).Study design Prospective randomized experimental trial.Animals Thirty-two adult crossbred cats, weighing 2.7 +/- 0.4 kg.Methods the cats were sedated with intramuscular (IM) methotrimeprazine (0.5 mg kg(-1)) and buprenorphine (0.005 mg kg(-1)), followed 30 minutes later by induction of anesthesia with intravenous (IV) thiopental (12.5-20 mg kg(-1)). An ET was used in 16 cats and an LMA in the remaining 16 animals. Anesthesia was maintained with 0.5 minimum alveolar concentration (0.6%) of halothane in oxygen using a Mapleson D breathing system. Cats in both groups were further divided into two equal groups (n = 8), undergoing either SV or CV. Neuromuscular blockade with pancuronium (0.06 mg kg(-1)) was used to facilitate CV. Heart and respiratory rates, direct arterial blood pressure, capnometry (PE'CO2) and arterial blood gases were measured. Gastric reflux and possible aspiration was investigated by intragastric administration of 5 mL of radiographic contrast immediately after induction of anesthesia. Cervical and thoracic radiographs were taken at the end of anesthesia. Data were analyzed using ANOVA followed by Student-Newman-Keuls, Kruskal-Wallis or Friedman test where appropriate.Results Values for PaCO2 and PE'CO2 were higher in spontaneously breathing cats with the LMA when compared with other groups. Values of PaO2 and hemoglobin oxygen saturation did not differ between groups. Gastroesophageal reflux occurred in four of eight and two of eight cats undergoing CV with ET or LMA, respectively. There was no tracheal or pulmonary aspiration in any cases.Conclusions and clinical relevance the use of an LMA may be used as an alternative to endotracheal intubation in anesthetized cats. Although aspiration was not observed, gastric reflux may occur in mechanically ventilated animals.
Keywords: airway; cat; endotracheal intubation; gastroesophageal reflux; laryngeal mask